Theoretical Foundation On Women Trafficking In Malaysia: A Legal Implication - Rahim, Rohani Abdul; Fendi, Fieza Fazlin; Makanah, Herlina; Rostamzadeh, Ehsan (Universiti Sains Malaysia, 2016)

(untitled)
Malaysia being a semi-developed country is attracting people from all corners of the world and this has caused people to migrate for work and other purposes. This also opened the doors to human trafficking and human smuggling activities that had blemished the country's reputation when ranked successively tier 3 and 2 in TIP (Trafficking In Persons) Report. Being aware of the problem, the country enacted the Anti-Trafficking in Persons and Anti-Smuggling of Migrant Act 2007 (amend.2012) but the enforcement has yet to be effective enough to stop completely sexual exploitation syndicates via trafficking in persons. Particularly, women and young girls were lured into becoming sex workers and domestic labour market. There are numerous theoretical foundations that explain why women are being trafficked and victimized as sex workers globally. Feminist economics, have proposed that supply of sex work is rooted in absence of economic alternatives, and that prohibitionist policies, both on the supply and the demand side, worsen working conditions and health of sex workers. Whereas migration theories are built differently based on comparison of wage differentials, employment differentials or, more broadly, living standard differentials between origin and destination countries. Nature of business that manipulated vulnerable conditions such as youth; gender; poverty; ignorance; social and cultural exclusion; political instability, war, and conflicts, discriminatory social, cultural, and legal frameworks; and ongoing demand. This paper presentation will firstly, explain the Women Trafficking activities and prevention efforts by the enforcers. Secondly, it focuses on what causes women trafficking and the underlying theoretical foundations that resulted in the sexual exploitation of women. Finally, the paper dwells on how the Malaysian laws protect women from being trafficked and sexually exploited as sex workers.